2018
DOI: 10.1002/cjce.23204
|View full text |Cite
|
Sign up to set email alerts
|

Three different periods of CO2 dissolution into a light crude oil

Abstract: In this paper, phase behaviours and mass‐transfer mechanisms of a Bakken light crude oil‐CO2 system are studied. A series of PVT tests of the light crude oil‐CO2 system are conducted to measure CO2 solubilities, oil‐swelling factors, and CO2‐saturated oil densities at different equilibrium pressures and the actual reservoir temperature of Tres = 56.0 °C. Five CO2 diffusion tests in the light crude oil are performed at five different initial test pressures (Pi = 4.1, 5.2, 6.3, 7.7, and 9.0 MPa) and Tres = 56.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…However, after the onset of convection, the curve deviates, resulting in m = 2C sat A √ D c (t − t c )/π (dashed line) to be the best fit, with an effective diffusion coefficient of D c = 30D and t c = 160 s as the virtual time origin. Compared to other authors, who report finding D c /D ∼ 10 2 or 10 3 for experiments conducted in varying PVT or Hele-Shaw cells, this seems reasonable as variations in experimental conditions and cell configuration differences appear to severely affect the obtained effective diffusion coefficients [20][21][22][23][24].…”
Section: Intensity and Concentration Profilessupporting
confidence: 56%
See 1 more Smart Citation
“…However, after the onset of convection, the curve deviates, resulting in m = 2C sat A √ D c (t − t c )/π (dashed line) to be the best fit, with an effective diffusion coefficient of D c = 30D and t c = 160 s as the virtual time origin. Compared to other authors, who report finding D c /D ∼ 10 2 or 10 3 for experiments conducted in varying PVT or Hele-Shaw cells, this seems reasonable as variations in experimental conditions and cell configuration differences appear to severely affect the obtained effective diffusion coefficients [20][21][22][23][24].…”
Section: Intensity and Concentration Profilessupporting
confidence: 56%
“…Moreover, in the regimes where convection is contributing to the mass transport, apparent diffusive behavior is observed, albeit with a much higher effective diffusion coefficient. Depending on the experimental conditions, this effective diffusion coefficient can be several orders of magnitude bigger in comparison to the expected diffusive counterpart under similar experimental conditions [20][21][22][23][24]. However, little explanation has been given as to what drives the different observed regimes, the transitions between the regimes and why the system still appears to behave in a diffusive manner.…”
Section: Introductionmentioning
confidence: 96%
“…Above the extraction pressure, the crude oil composition changes due to the extraction of intermediate components of the crude oil into the CO 2 phase. Figure c compares the diffusion coefficient data (at 23 and 50 °C) determined using the microfluidic method developed in this study with the data reported elsewhere obtained by pressure decay and pendant drop experiments. The literature reported values are all from light oil. While there is no exact match between the fluid samples, test conditions, and experimental methods, the results obtained here were in good agreement with the literature data.…”
Section: Resultsmentioning
confidence: 66%
“…n-Alkanes with longer carbon chains have a larger viscosity reduction with increasing amounts of dissolved CO 2 . Gu et al measured viscosity of the light crude oil and reported a value of 1.48 cP at the atmospheric pressure and the reservoir temperature of 329 K. 56…”
Section: Resultsmentioning
confidence: 99%